Fifteen years of elasmobranchs trade unveiled by DNA tools: Lessons for enhanced monitoring and conservation actions - Alvarenga, Marcela; Bunholi, Ingrid Vasconcellos; de Brito, Gustavo Reis [UNESP]; Siqueira, Marcos Vinícius Bohrer Monteiro; Domingues, Rodrigo Rodrigues; Charvet, Patricia; Foresti, Fausto [UNESP]; Solé-Cava, Antonio Mateo; da Cruz, Vanessa Paes [UNESP] (Elsevier, 2024)
The trade of elasmobranchs (sharks and rays) in Brazil threatens the country's rich endemic biodiversity. The present study explored the use of DNA-based tools to monitor the Brazilian elasmobranch trade, focusing on their role in identifying processed products and supporting conservation efforts. A systematic search of literature was conducted and included 35 peer-reviewed papers published between 2008 and 2023. A shift from the development of DNA-based tools to direct trade applications has been observed since 2015. Molecular identification challenges, including costly sequencing and limited resources in national databases, were identified along with proposed solutions, such as protocol optimization and exploration of cost-effective alternatives. Biases in trade analysis papers, particularly the lack of research in the Northeast Region of Brazil, and issues with sample sizes were evident. Species identified using DNA-based tools included the critically endangered Scalloped Hammerhead Shark (Sphyrna lewini), which appeared in 46 % of the evaluated papers, followed by the Blue Shark (Prionace glauca), and several others threatened species, such as the critically endangered and endemic Brazilian Guitarfish (Pseudobatos horkelii) and the recently categorized as vulnerable Sharpnose Shark (Rhizoprionodon porosus). Other species were reassessed by IUCN, including previously non-threatened species that are now at risk, emphasizing the need for fisheries management, trade monitoring and conservation measures. Our findings highlight the importance of continued genetic monitoring to analyze market trends and adjust legislation, encouraging compliance with frequent inspections to enhance wildlife conservation. We also identified gaps in research and recommended strategies for accurate species identification, broader investigation, and effective management.
Keywords: Brazilian trade; Conservation genetics; DNA-based tools; Elasmobranchs (sharks and rays); Endemic species; Forensics